The dogma of the Holy Trinity in the Letter of Eznik of Kołb “To the Blessed Archimandrite Mashtots” - Arthur Matevosyan (Banber Arevelagitut'yan Instituti)
“The Book of Letters” contains Eznik of Kołb's letter “To the Blessed Archimandrite Mashtots”, which is one of the key documents reflecting the creed of the Armenian Church of the 5th century. The dogmatic system of the Armenian Church is based on the Niceno- Constantinopolitan creed, according to which God is one essence and three Hypostases. It means that the one God is eternally personified in the Hypostases of Father, Son, and Holy Spirit. Each Hypostasis contains the fullness of the divine essence, so the three Hypostases are equally perfect God, yet not three Gods, but one God. It is so, because the divine essence is one and does not exist independently of the Hypostases. The Christian doctrine of the God-Man makes sense only if the divine nature of the Incarnate Word in Jesus is recognized. For this, it is necessary that all the Hypostases of the Holy Trinity are consubstantial and equally perfect. The Son is as much God as the Father and has all the attributes attributed to the Father. Although the Father is the cause of the Son's existence, the birth of the Son cannot in any way be considered the result of an act of the Father's will. It is an eternal and ineffable birth that necessarily takes place in the transcendent depths of the divine nature. The only begotten Son is begotten of the Father in eternity, and has all the attributes of the Father except that He is not begotten. In the same eternity, the Holy Ghost proceeds from the Father. There is no temporal sequence between the Hypostases. They are coeternal and have the same nature, power and will.